Mídias táticas no Brasil: dinâmicas de informação e comunicação - Santos, Anne Danielle Soares Clinio dos (2011)
This paper aims to contribute to studies about resistance, offering an analysis of the limits and possibilities of the use of Internet by dissident groups as the digital information and communication networks are becoming central in social life organization, production processes and accumulation of wealth. The tactical media concept, elaborated by Garcia and Lovink (1997), is understood as an attempt to highlight new forms of political action made possible by the popularization of information and communication technologies (ICTs), in order to introduce an analysis of informational dynamics and communication in the World Wide Web by tactical media groups in Brazil. The research about Internet use by tactical media groups in Brazil reveals local characteristics and a concentrated use for activism purposes, as a way of sharing information, mobilization and coordination of activities by individuals or groups with a common goal. Four examples of action are detailed: Movimento dos Sem Satélite (Satelliteless Movement MSST), parody blog Falha de São Paulo, assina: do texto ao contexto , project by Cícero Dias da Silva and the idea of MetaReciclagem This work adopts the approach of Operaism theories, in which the changes originated by the biopolitical production are not restricted to the economic field, but also transforms ontological and social fields - which are considered an opportunity for groups interested in promoting social transformation